Discussion on cable-strut systems of the suspen-dome structures. Issue 1 (March 2023) - Liu, Renjie; Li, Muqiao; Cheng, Tianchen
According to the architectural requirements, the roof structure of a large-span gymnasium adopts the suspen-dome structure. In the scheme selection stage of the pre-stressed cable-strut system at the bottom part of the suspen-dome structure, a Levy-type scheme and a Loop-free scheme are established. The finite element models are established, and the static analysis under the design loads, the whole process analysis of load-displacement, and the dynamic response analysis after accidental cable break are carried out. The architectural expression of the two schemes are discussed. The component material consumption, the structural stiffness, the tension distribution characteristics, and the static bearing capacity of the two schemes are discussed. The failure mode and the progressive collapse resistance of the two schemes after accidental cable break are also discussed. The results show that the Loop-free scheme requires significantly less in terms of component material consumption than the Levy-type scheme. The static failure mode of the two schemes is strength failure, but the Loop-free scheme has greater bearing capacity. The Loop-free scheme has greater structural stiffness, lower cable forces, and uniformly distributed cable forces in each layer, and lower stress on the top reticulated shell members. Neither of the two schemes experience progressive collapse after accidental cable break. Due to the rupture in the loop cable of the Levy-type scheme, the rigidity of the rear region decreases greatly, and the cable force loss is large. On the contrary, internal force redistribution occurs in the Loop-free cable scheme and the cable force loss is not obvious, hence the progressive collapse resistance is better than that of the Levy-type scheme.